Clinical significance of direct cytotoxicity and toxigenic culture in Clostridium difficile infection. (February 2016) - Reigadas, E.; Alcalá, L.; Marín, M.; Muñoz-Pacheco, P.; Catalán, P.; Martin, A.; Bouza, E.
Abstract: Background: Clostridium difficile infection (CDI) is the leading cause of hospital-acquired diarrhoea in developed countries. Although an optimal diagnosis is crucial, laboratory diagnostics remain challenging. Currently, the reference methods are direct cytotoxicity assay and toxigenic culture; however there is controversy in the interpretation of discordant results of these tests. Objective: The aim of our study was to determine the clinical significance of detecting C . difficile only by toxigenic culture with a negative direct cytotoxicity assay. Methods: We conducted a prospective study in which patients aged >2 years with CDI were enrolled and monitored at least 2 months after their last episode. Samples were tested by both cytotoxicity assay and toxigenic culture. Results: During the 6-month study period, we identified 169 episodes meeting CDI criteria that had been tested by both assays, out of which 115 were positive for both cytotoxicity assay and toxigenic culture, and 54 CDI episodes (31.9%) were positive only by toxigenic culture. Overall, patients median age was 71.3, 50.9% were male and the most frequent underlying disease was malignancy. The comparison of CDI episodes positive for both assays and by toxigenic culture only revealed the following, respectively: mild CDI (77.4% vs 94.4%; p = 0.008), severe CDI (21.7% vs 5.6%; p = 0.008), severe complicated (0.9% vs 0.0%; p = 1.000), pseudomembranous colitis (1.7% vs 1.9% p = 1.000), recurrence (17.4% vs 14.8%; p = 0.825), overall mortality (8.7% vs 7.4%; p = 1.000) and CDI related mortality (2.6% vs 0%; p = 0.552). Conclusion: CDI episodes positive by cytotoxicity assay were more severe than those positive only by toxigenic culture, however there were a significant proportion of CDI cases (31.9%) that would have been missed if only cytotoxicity had been considered as clinically significant for CDI treatment, including severe CDI cases. Our data suggest that a positive test by toxigenic culture with a negative result for cytotoxicity should not be interpreted as colonization. Highlights: CDI episodes positive by cytotoxicity assay were more severe than those positive only by toxigenic culture. However, 1/3 of true CDI would have been missed due to a negative cytotoxicity, including severe and pseudomembranous colitis. Toxigenic culture positive/cytotoxicity negative episodes should not be ruled out as colonization without clinical assessment.